Cinema VR: concepções teóricas e técnicas sobre a fruição do espectador em narrativas cinematográficas em 360 graus - Silva, Iury Matheus Costa (2021)
The issue of the dissertation revolves around understanding how it is possible to attract the attention of the viewer in 360-degree films, in order to enable the construction of a narrative process and a minimum understanding by the public about the story being told. Seeking to have an understanding of what mise-en-scène is and how it relates to cinema and VR cinema itself, we seek as a basis the studies of Junior (2013) and Bordwell and Thompson (2006). Based on this, we highlight that this dissertation is composed of two parts, the first consists of a study on miseen-scène in cinema and how it is applied and related to virtual reality, in order to assist in the construction of a more accurate understanding of what Virtual Reality Cinema is. The second part, in turn, sought to develop an initial framework that would assist the 360-degree film production team to attract viewers' attention so that they have a minimal understanding of the story and, for that, a literature review was carried out. , in order to gather and understand the techniques used, as well as a film analysis of the works Faoladh (2018) and Help (2016) in order to observe the techniques and the way that these films used to guide the viewer's attention and develop their narratives.